Spatial differences in Hungarian medical tourism supply based on service providers’ online presence - Michalkó, Gábor; Rátz, Tamara; Hinek, Mátyás (Hungarian Geographical Bulletin, 2012)
Medical tourism is a relatively new fi eld in Hungarian health tourism development, with significant growth potential. The paper presents the findings of an Internet-based research project that aims to explore the fundamental characteristics of medical tourism in Hungary. The key issues discussed in the framework of the analysis are the interrelationship of healthcare and tourism on the one hand, and the spatial distribution of medical services and treatments on the other hand. The research identified four main segments of the Hungarian medical tourism product: (1) the international tourism- and expatriate-oriented healthcare of Budapest, (2) the socio-geographically determined medical practices located near the Austrian border, (3) the combination of traditional spa culture and latest medical technology in the classical spa towns, and (4) the fast developing regional centres of the periphery